EFFECTIVENESS OF IMPLEMENTATION OF ARTIFICIAL INTELLIGENCE TECHNOLOGY IN THE ACTIVITIES OF HIGHER EDUCATION INSTITUTIONS - Marasulova Zulaykho Abdullayevna; Sharipova daughter of Nafisa Omonjon (Galaxy International Interdisciplinary Research Journal, 2024)
In this article, the implementation of artificial intelligence technology in the higher education system of our republic, based on the analysis of the possibilities of artificial intelligence, the implementation of artificial intelligence technology in the activities of higher education institutions should be implemented. proposals are given for determining the initial measures, development of ways to effectively use the possibilities of artificial intelligence platforms in the higher education system.